Generating high-order optical and spin harmonics from ferromagnetic monolayers - G. P. Zhang (Nature Portfolio, 2018)
High-order harmonic generation (HHG) has been explored in different kinds of solids except magnetic materials. Here the authors theoretically predict that the HHG in ferromagnetic Fe thin films is sensitive to the spin–orbit coupling and carries band structure information.